(untitled) (Journal of the College of Basic Education, 2022)
Image segmentation technique refers to the process of partitioning a digital image into multiple segments i.e. set of pixels, pixels in a region are similar according to some homogeneity criteria such as color, intensity or texture, so as to locate and identify objects and boundaries in an image. Several general-purpose algorithms and techniques have been developed for threshold image segmentation. In this paper we introduce two segmentation algorithms the first one is histogram and iterative method. The histogram algorithm uses minimum two peaks in gray image to determine constant threshold(global) ,while the iterative algorithm uses variable threshold(local) to segment image, and finally get binary image. with application in programming environment Matlab. Next are describing some advantage and disadvantages of those algorithms.